ASSOCIATION OF PREDIABETES WITH RETINAL MICROVASCULATURE ON SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY IN THE ELDERLY: OTASSHA Study. Issue 6 (June 2022) - Wang, You; Toyama, Taku; Hashimoto, Yohei; Kawai, Hisashi; Azuma, Kunihiro; Shiraya, Tomoyasu; Kato, Satoshi; Watanabe, Yutaka; Hirano, Hirohiko; Fujiwara, Yoshinori; Ihara, Kazushige; Kim, Hunkyung; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: To investigate the retinal microvasculature in the elderly persons with prediabetes mellitus (preDM) and type 2 DM. Methods: This cross-sectional study included a total of 452 eyes without retinal pathologies of 301 elderly volunteers aged ≥65 years, and they were categorized into nonDM (225 eyes), preDM (177 eyes), and DM (50 eyes) groups based on their HbA1c. Fundus photography, swept-source optical coherence tomography and angiography, and comprehensive systemic examinations were conducted. Vessel density (VD) and foveal avascular zone in superficial and deep retinal microvasculature were investigated for their association with DM stages using linear mixed model. Results: Superficial VD (sVD) mean values in nonDM, preDM, and DM groups were 35.2%, 34.9%, and 34.8%, respectively. sVD in preDM was equivalent to sVD in DM, whereas significantly lower compared with sVD in nonDM (difference [95% CI] −0.19 [−0.33 to −0.049], P = 0.009). Deep VD (dVD) mean values in nonDM, preDM, and DM groups were 35.0%, 35.0%, and 34.4%, respectively. dVD in preDM was equivalent to dVD in nonDM, whereas significantly higher compared with dVD in DM (difference [95% CI] 0.31 [0.046–0.57], P = 0.02). There was no significant association between foveal avascular zone area and DM stages. Conclusion: Retinal microvasculature may be affected at the prediabetic stage in the elderly.